PENGARUH KEPEMIMPINAN TERHADAP PENGEMBANGAN SUMBER DAYA MANUSIA DI LINGKUP SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN MAMUJU UTARA - Hijriah, Hijriah (Katalogis, 2016)
The aim of this study; (1) to determine the effect simultaneously leadership on human resource development in the scope of the Secretariat of the Regional Representatives Council of North Mamuju regency; (2) to determine the effect of partially leadership to the development of human resources in the scope of the Secretariat of the Regional Representatives Council of North Mamuju regency. Leadership theory developed using olehHersey and Blanchard in Gibson et al. (2010: 34), while the development of human resources using the theory of Armstrong (2006: 535). This type of research is quantitative descriptive and verification approach. This study population pegawaidi scope of the Secretariat of the Regional Representatives Council of North Mamuju regency numbering 70 people and drawn using census to 69 respondents because the leadership is not included in the sample. Data collection techniques include observation, questionnaires, and documentation, while the technique of data analysis using multiple linear regression. The results showed; (1) the influence of the simultaneous leadership on human resource development in the scope of the Secretariat of the House of Representatives District North Mamuju determined by saying (telling), sell (selling), participate (participating), and delegates (delegating), with much influence 62 , 1% and a degree of association "strong"; (2) The partial effect of leadership on human resource development in the scope of the Secretariat of the Regional Representatives Council of North Mamuju regency is determined by the dimensions of said (telling) a significant effect on the development of human resources; dimensions selling (selling) a significant effect on the development of human resources; dimensional participate (participating) significantly affects the development of human resources; and dimensions delegate (delegating) significantly affects the development of human resources